Mo-La(2)O(3) Multilayer Metallization Systems for High Temperature Surface Acoustic Wave Sensor Devices - Menzel, Siegfried B. (Materials (Basel), 2019)
Developing advanced thin film materials is the key challenge in high-temperature applications of surface acoustic wave sensor devices. One hundred nanometer thick (Mo-La [Formula: see text] O [Formula: see text]) multilayer systems were fabricated at room temperature on thermally oxidized (100) Si substrates (SiO [Formula: see text] /Si) to study the effect of lanthanum oxide on the electrical resistivity of molybdenum thin films and their high-temperature stability. The multilayer systems were deposited by the magnetron sputter deposition of extremely thin (≤1 nm) La interlayers in between adjacent Mo layers. After deposition of each La layer the process was interrupted for 25 to 60 min to oxidize the La using the residual oxygen in the high vacuum of the deposition chamber. The samples were annealed at 800 [Formula: see text] C in high vacuum for up to 120 h. In case of a 1 nm thick La interlayer in-between the Mo a continuous layer of La [Formula: see text] O [Formula: see text] is formed. For thinner La layers an interlayer between adjacent Mo layers is observed consisting of a (La [Formula: see text] O [Formula: see text]-Mo) mixed structure of molybdenum and nm-sized lanthanum oxide particles. Measurements show that the (Mo-La [Formula: see text] O [Formula: see text]) multilayer systems on SiO [Formula: see text] /Si substrates are stable at least up to 800 [Formula: see text] C for 120 h in high vacuum conditions.